Sulfate radical-based oxidation for sludge treatment: A review - Liu, Changgeng; Wu, Bin; Chen, Xiao'e (Chemical engineering journal (Lausanne, Switzerland : 1996), 2018)
[Display omitted] •Activated PDS and PMS oxidation is widely applied for sludge treatment.•Sludge dewaterability and disintegration as the focus are well summarized.•Different activators for PDS and PMS activation are presented and discussed.•Metal solubilization and micropollutant degradation in sludge are reviewed. An ever-increasing amount of wasted activated sludge is the greatest challenge to wastewater treatment plants on both the economic and environmental sides. Within the last five years, great attention has been attracted to apply sulfate radical (SO4−)-based oxidation for sludge treatment. Based on the published studies, an extensive review about SO4--based oxidation applied for sludge disintegration, dewaterability enhancement, metal solubilization, and micropollutant degradation in the sludge is presented. Focus is placed on sludge dewaterability and disintegration by the activation of peroxymonosulfate (PMS) and peroxydisulfate (PDS) with different activators. Knowledge gaps are pointed out and discussed, more work should be carried out to further supplement and optimize SO4--based oxidation processes for highly-efficient and cost-effective treatment in the practical sludge systems though their potentials on sludge treatment have been demonstrated.